Why and How Is Compassion Necessary to Provide Good Healthcare? Comments From an Academic Physician; Comment on "Why and How Is Compassion Necessary to Provide Good Quality Healthcare?" - Christos Lionis (Kerman University of Medical Sciences, 2015)
This is a short commentary to the editorial issued by Marianna Fotaki, entitled: "Why and how is compassion necessary to provide good quality healthcare." It introduces the necessity of a more cognitive approach to explore further the determinants of behavior towards compassionate care. It raises questions about the importance of training towards a more patient-care and values driven healthcare system.